Altered Prefrontal and Hippocampal Function During Verbal Encoding and Recognition in People With Prodromal Symptoms of Psychosis - Allen, Paul; Seal, Marc L.; Valli, Isabel; Fusar-Poli, Paolo; Perlini, Cinzia; Day, Fern; Wood, Stephen J.; Williams, Steven C.; McGuire, Philip K. (Schizophrenia bulletin, 2011)
Despite robust evidence of hippocampal abnormalities in schizophrenia, it is unclear whether hippocampal dysfunction predates the onset of psychosis. We used functional magnetic resonance imaging to investigate hippocampal function in subjects with an at-risk mental state (ARMS). Eighteen subjects meeting criteria for an ARMS and 22 healthy controls, matched for age, gender, and premorbid IQ, were scanned while performing a version of the Deese-Roediger-McDermott false memory task. During an encoding phase, subjects read lists of words aloud. Following a delay, they were presented with 24 target words, 24 semantically related lure words, and 24 novel words and required to indicate if each had been presented before. Behaviorally, the ARMS group made more false alarm responses for novel words than controls (P = .04) and had a lower discrimination accuracy for target words (P = .02). During encoding, ARMS subjects showed less activation than healthy controls in the left middle frontal gyrus, the bilateral medial frontal gyri, and the left parahippocampal gyrus. Correct recognition relative to false alarms was associated with differential engagement of the hippocampus bilaterally in healthy controls, but this difference was absent in the ARMS group. The ARMS was associated with altered function in the medial temporal cortex, as well as in the prefrontal regions, during both verbal encoding and recognition. These neurofunctional differences were associated with diminished recognition performance and may reflect the greatly increased risk of psychosis associated with the ARMS.